PERAN KELOMPOK SADAR WISATA (POKDARWIS ) DALAM KELESTARIAN KAWASAN JALUR PENDAKIAN GUNUNG SINGGALANG VIA PANDAI SIKEK - Rachman, Erik; Marnelly, T. Romi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research was conducted in Mount Singgalang, Pandai Sikek, Tanah Datar Regency, West Sumatra Province. The objectives of this study were to determine: 1) The role of Travel Awareness Group (POKDARWIS) in the preservation of the Singgalang hiking trail area via Pandai Sikek. 2) The thing that hinders the Travel Awareness Group (POKDARWIS) from carrying out its role in the preservation of the Mount Singgalang hiking trail area via Pandai Sikek. This study uses a descriptive qualitative method by taking 7 people as informants, namely 5 members of POKDARWIS, 1 chairman of BUMNAK, and 1 person from the surrounding community. This research uses purposive method and uses observation, interview, and documentation techniques. The results of this study indicate that POKDARWIS as the manager has the task of carrying out the tourism potential in Pandai Sikek through the Mount Singgalang climbing route. POKDARWIS has a role as a motivator for Tourism Awareness, Sapta Pesona in the regional environment in tourist destinations, a driving force for Tourism Awareness and Sapta Pesona in regional environments in tourist destinations. The normative role that appears in the implementation in the field starts from a) the role of education is an invitation and appeal to preserve nature b) the control role is POKDARWIS as a manager in maintaining the beauty of the hiking trail area c) the role of information as a provider of information and a means of communication about everything related with hiking trails. The sustainability of the hiking trail area depends on the performance of POKDARWIS as a manager in managing tourism, especially when climbing activities are busy and difficult to control so that it becomes an obstacle for POKDARWIS in maintaining the beauty of the environment. Internal constraints experienced by POKDARWIS such as lack of skills and understanding of members in carrying out their roles as POKDARWIS and other activities outside POKDARWIS activities. External obstacles come from climbers and also support from Nagari.Keywords: POKDARWIS, Preservation of the Hiking Trail Area